(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Laminar flow of fluids is one of the most common forms of motion in oilfield practice. In such a flow regime of fluid, the determination of velocity-flow rate performance which takes into account the rheological properties of the fluid is of great importance for the development of hydraulic criteria. On the other hand, from the moment of the beginning of fluid motion in the pipe, a certain time is required to ensure the steady flow of fluid, i.e. independence of its parameters on time. The issues of diagnosing steady-state characteristics in laminar flow of both Newtonian and non-Newtonian fluids are of particular relevance. In this paper, the velocity distribution along the cross-section of a pipe in laminar flow of Newtonian and non-Newtonian fluids is studied while taking into consideration rheological factors, and the change of flow rate is investigated. Determination of the time of transition to the steady-state flow regime and parameters affecting the variation of this time are shown.